Incidence and mortality from malignant mesothelioma 1982–2020 and relationship with asbestos exposure: the Australian Mesothelioma Registry. Issue 4 (8th February 2023) - Walker-Bone, Karen; Benke, Geza; MacFarlane, Ewan; Klebe, S; Takahashi, Ken; Brims, Fraser; Sim, Malcolm Ross; Driscoll, Tim R
Abstract : Objectives: Malignant mesothelioma is an uncommon cancer associated with asbestos exposure, predominantly occupational. Asbestos has been banned in Australia since 2003 but mesothelioma has a long latency and incident cases continue to present. The Australian Mesothelioma Registry was incepted to collect systematic data about incidence and mortality alongside asbestos exposure. Methods: Benefiting from the Australian national system of cancer notification, all incident cases of mesothelioma in all states and territories are fast-tracked and notified regularly. Notified patients are contacted asking for consent to collect exposure information, initially by postal questionnaire and subsequently by telephone interview. Age-standardised annual incidence rates and mortality rates were calculated. Asbestos exposure was categorised as occupational, non-occupational, neither or, both; and as low, or high, probability of exposure. Results: Mesothelioma incidence appears to have peaked. The age-standardised incidence rates have declined steadily since the early 2000s (peaking in males at 5.9/100 000 and in all-persons at 3.2/100 000), driven by rates in males, who comprise the majority of diagnosed cases. Rates in women have remained fairly stable since that time. Age-standardised mortality rates have followed similar trends. Mesothelioma remains the most common in those aged over 80 years. Nearly all (94%) cases were linked with asbestos exposure (78% occupational in men; 6.8% in women). Conclusions: With effective control of occupational asbestos use, the decline in age-standardised incidence and death rates has occurred. Incidence rates among women, in whom occupational asbestos exposure is rarely detectable, remain unchanged, pointing to the role of household and /or environmental asbestos exposure.